Holter-determined arrhythmias in young elite athletes with suspected risk: Insights from a 20-year experience - Boraita, Araceli; Heras, María-Eugenia; Valenzuela, Pedro L.; Diaz-Gonzalez, Leonel; Morales-Acuna, Francisco; Alcocer-Ayuga, María; Bartolomé-Mateos, Sonia; Santos-Lozano, Alejandro; Lucia, Alejandro (Frontiers in Cardiovascular Medicine, 2022)
Purpose. We assessed the occurrence of rhythm alterations in elite athletes with suspected risk using Holter monitoring, and the association of Holter-determined rhythm alterations with echocardiographic findings. Methods. A large cohort of Spanish elite athletes (N=6579, 34% female) underwent in-depth cardiological examination (including echocardiographic evaluation, and resting and exercise electrocardiogram [ECG]) between 01/02/1998-12/31/2018. Holter monitoring was performed in those reporting cardiovascular symptoms, with suspicion of cardiac structural abnormalities potentially associated with dangerous arrhythmias, or with resting/exercise ECG features prompting a closer examination. We assessed the occurrence of cardiac rhythm alterations, as well as the association between echocardiography-determined conditions and rhythm alterations. Results. Most athletes (N=5925) did not show any sign/symptom related to arrhythmia (including normal resting and exercise/post-exercise ECG results) whereas 9.9% (N=654; 28% female; median age, 24 years [interquartile range 19–28]; competition experience [mean±SD] 10±6 years) met the criteria to undergo Holter monitoring. Among the latter, sinus bradycardia was the most common finding (present in 96% of cases), yet with a relatively low proportion of severe (<30bpm) bradycardia (12% of endurance athletes during night-time). Premature atrial and ventricular beats were also common (61.9% and 39.4%, respectively) but sinus pauses ≥3sec, high-grade atrioventricular blocks, and atrial fibrillation/flutter were rare (<1%). Polymorphic premature ventricular contractions (PVC, 1.4%) and idioventricular rhythm (0.005%) were also rare. PVC couplets were relatively prevalent (10.7%), but complex ventricular arrhythmias were not frequent (PVC triplets: 1.8%; sustained ventricular tachycardia: 0.0%; and nonsustained ventricular tachycardia: 1.5%). On the other hand, no associations were found between arrhythmias (including their different morphologies) and major cardiac structural alterations (including mitral prolapse). However, an association was found between mild mitral regurgitation and supraventricular (odds ratio 2.61; 95% confidence interval 1.08–6.32) and ventricular (2.80; 1.15–6.78; p=0.02) arrhythmias, as well as between mild or moderate mitral regurgitation and ventricular arrhythmias (2.49; 1.03–6.01). Conclusions. Irrespective of the sports discipline, ‘dangerous’ ventricular arrhythmias are overall infrequent even among young elite athletes who require Holter monitoring due to the presence of symptoms or abnormal echocardiographic/ECG findings, and do not seem to be associated with underlying serious cardiac structural pathologies.